Kingdom of the Netherlands-Curacao and Sint Maarten : 2014 Article IV Consultation-Staff Report; and Press Release. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Context: The union's current account deficit-the key economic vulnerability flagged in the previous (2011) consultation-has declined over the past few years, including thanks to fiscal adjustment in Curacao. But it remains large. Curacao's growth and job creation remain lackluster, due to weak competitiveness, adverse sectoral trends (e.g., in the international financial center), red tape, and rigid labor laws. Sint Maarten's tourism-based economy is recovering but remains vulnerable to shocks and suffers from weak administrative capacity-as underscored, for example, by weakening tax collection. Risks: Both Curacao and, especially, Sint Maarten are exposed to shifts in tourism demand. Curacao is vulnerable to the uncertain situation in Venezuela, its main trading partner. If long-discussed flexibility- and competitiveness-enhancing structural reforms are not implemented, both countries' capacity to absorb shocks may prove limited, and pressures on FX reserves and, ultimately, the peg may intensify. Policy recommendations: Fiscal policies should entrench recent gains to facilitate continued external adjustment (especially in Curacao) and build buffers against shocks. Curacao should extend the reform of its pension system to public sector workers, further streamline its administrative apparatus, and address weak governance and finances in state companies. Sint Maarten needs to increase revenues to support an expanding administration, including through stronger tax collection and greater contribution from its profitable state companies. The common central bank must monitor closely the deterioration in banks' loan portfolios and refrain from direct financing of non-financial companies. It should also use more standard sterilization tools to control banks' excess liquidity. Urgent action is required to lower the cost of doing business and remove pervasive disincentives to both supply and demand of labor.